Impact of motivation on the job performance of public sector employees: the case of Morocco - Driss Elamalki; Abdelilah Kaddar; Nadia Beniich (Future Business Journal)
Abstract This study investigates the driving forces behind job performance in Morocco's public sector amid its latest reforms. Despite extensive research on motivation and job performance, the unique dynamics within this sector, particularly following recent legislative changes, still need to be explored. This study links job performance to an incentive-based system by examining the roles of both intrinsic and extrinsic motivations in enhancing employee performance. Employing qualitative methodology, this study explores how incentives and motivation impact job performance. Data collected via a structured questionnaire are analyzed using structural equation modeling to elucidate the connections between work performance, motivation, and incentives. These findings highlight the significance of transparent human resource policies, comprehensive incentive systems, appropriate performance metrics, and robust leadership in cultivating a motivated and high-performing workforce.